'EDL angels stand beside their men … not behind them': the politics of gender and sexuality in an anti-Islam(ist) movement. Issue 2 (23rd February 2017) - Pilkington, Hilary
ABSTRACT: This article revisits the view that women are absent or insignificant across the extreme right spectrum. It draws on ethnographic research with grassroots activists in the English Defence League to explore whether a new generation of populist radical right movements offers a gender politics and practice capable of appealing to women and LGBT constituencies. It critically interrogates claims that the movement has made real shifts in the openness to, and roles played by, women and LGBT activists and asks whether the adoption of gender equality and gay rights rhetoric reflects such change or is an essentially instrumental move. Finally it considers how gender and sexual politics are played out in everyday practice in the movement. It concludes that while openness to women and LGBT supporters and activists is more than the top-down imposition of a strategically useful ideology, attitudes and behaviours among activists remain highly diverse, ambivalent and often conflicted.